RESULTS OF EXPEDITIONS CARRIED OUT BY KRYMSK EXPERIMENT BREEDING STATION OF VIR TO COLLECT WILD AND RUN-WILD FRUIT AND BERRY PLANTS IN SOUTHERN REGIONS OF RUSSIA - G. V. Eremin; V. N. Podorozhnyi (Труды по прикладной ботанике, генетике и селекции)
Since the beginning of the 2000s, the ecological and climatic situation in southern regions of Russia has deteriorated significantly due to the increased anthropogenic impact. In particular, the Republic of Crimea, especially its steppe zone, has been experiencing a real ecological disaster since 2016 because of water deficiency due to the drying up of the North-Crimean Canal after it has been blocked by Ukraine. All this makes it urgent to search for and collect wild and run-wild plant species in their natural habitats, and conserve them in controlled conditions at VIR’s branches.  Krymsk Experiment Breeding Station has developed a long-term plan for conducting expeditions to collect stone fruit and berry genetic resources for augmenting VIR’s collections. This plan is being implemented on a regular basis. The goal of this work is to explore natural habitats, collect fruit and berry plant diversity, further maintain it in field collections at Krymsk Experiment Breeding Station, and comprehensively study it with the aim of identifying sources of economically important traits for creating new highly adaptive and technologically advanced varieties and rootstocks.  Expeditions were conducted in 2016–2018 in southern areas of the steppe zone and northern steppe regions of Krasnodar Territory, Volgograd Province, in southeastern regions of Rostov Province, and in the Republic of Crimea. It was established by field surveys that wild stone fruit plants are found everywhere much less frequently than it was observed in previous years, when similar expeditions were launched to these areas. All in all, this work resulted in collecting 222 samples of typical representatives of the studied fruit and berry species from the areas of their natural occurrence. All of them were placed in the nursery of Krymsk Experiment Breeding Station, got established well, and thus augmented the VIR collection of fruit and berry crops.  In view of the observed tendency of the natural distribution areas being reduced for a number of wild stone fruit species due to global climatic changes and recent increase of the anthropogenic impact, it is necessary to continue conducting expeditions to collect genotypes, especially of such species as ground cherry and Russian almond. In the near future, it is planned to explore the mountainous and Caspian regions in the Republic of Dagestan.